Lingual supplementation may not be required after articaine buccal infiltration anesthesia for lower molar extraction: A clinical comparative study - Omer Waleed Majid; Zaid Abdulazeez Muhammad (Universidad de Concepción., 2022)
Purpose: To investigate the anesthetic effectiveness of buccal infiltration (BI) versus buccal plus lingual infiltration (BI+LI) of 4% articaine for intra-alveolar extraction of erupted mandibular molar teeth Material and Methods: Eighty patients were included in this prospective clinical study. They were randomly divided into 1 of 2 equal groups: the 1st group received BI of 4% articaine 1.8 ml and LI of 0.5 ml, while the 2nd group received 4% articaine 1.8 ml BI plus 0.5 ml LI of normal saline. Another 1.8 ml articaine BI was given if initial anesthesia was inadequate. Outcome variables included pain, which was rated by patients at 3 intervals using visual analogue scale, and lingual anesthesia and patients' satisfaction which were measured using 5-score verbal rating scale. Data analyses used were descriptive statistics, t test, χ2 test, and Pearson's correlation coefficient. P-value value less than 0.05 was considered significant Results: There were 46 females and 34 males and the mean age was 35.3 years. All outcome variables were comparable between the two study groups (p˃0.05). Anesthesia was successful in 78% and 88% of cases in the (BI) and (BI+LI) groups respectively with no significant difference (p=0.2392). The mean articaine volume used was 2.5 ml and 2.87 ml respectively without significant difference (p=0.090). Conclusion: The anesthetic efficacy of (BI) alone and (BI+LI) of 4% articaine was comparable. When given in an adequate dose, articaine (BI) alone could be justified as an anesthetic option for the intra-alveolar extraction of mandibular molar teeth.